cho a+b+c = 3 rút gọn biểu thức (a^3+b^3+c^3-3abc)/((a-b)^3+(b-c)^3+(c-a)^3)
cho a+b+c = 3 rút gọn biểu thức (a^3+b^3+c^3-3abc)/((a-b)^3+(b-c)^3+(c-a)^3)
Aii hộ với!?? ~_~
Cho a+b+c=B. Rút gọn B=a^3+b^3+c^3-3abc/(a-b)^3+(b-c)^3+(c-a)^3
Cho a+b+c= 3
Rút gọn: A=\(\frac{a^3+b^3+c^3-3abc}{\left(a-b\right)^3+\left(b-c\right)^3+\left(c-a\right)^3}\)
a+b+b= 3. Rút gọn bểu thức
A= a^3+b^3+c^3-3abc / ( a-b )^3 + ( b-c )^3 + ( c-a )^3
Rút gọn biểu thức
\(\frac{\text{a^3+b^3+c^3-3abc}}{\text{a^2+b^2+c^2-ab-bc-ca}}\)
Rút gọn
\(B={a^3-b^3+c^3+3abc}\over {(a+b)^2+(b+c)^2+(c+a)^2}\)
cho a + b + c = 0. Rút gọn phân thức sau:
a3 + b3 + c3 -3abc
( a - b )3 + ( b - c )3 + ( c - a )3
cho a + b + c = 3. Rút gọn phân thức sau:
(a3 + b3 + c3 -3abc)/[( a - b )3 + ( b - c )3 + ( c - a )3]